Integrating Network Pharmacology and Metabolomics to Reveal the Immunomodulatory Mechanism of Ethnomedicine Rodgersia sambucifolia Hemsl - Zhou J; Wu Y; Lu Z; Wang Y (Dove Medical Press, 2024)
Jiayue Zhou,1,2 Yingxiang Wu,1,2 Zhiyan Lu,1,2 Yan Wang1,2 1Yunnan Provincial Key Laboratory of Entomological Biopharmaceutical R&D, Dali University, Dali, Yunnan Province, 671000, People's Republic of China; 2National-Local Joint Engineering Research Center of Entomoceutics, Dali University, Dali, Yunnan Province, 671000, People's Republic of ChinaCorrespondence: Yan Wang, Yunnan Provincial Key Laboratory of Entomological Biopharmaceutical R&D, Dali University, Dali, Yunnan Province, 671000, People's Republic of China, Tel +86 0872-2257401, Email jessica9428@sina.comPurpose: Rodgersia sambucifolia Hemsl (also known as Yantuo) is a traditional Chinese medicine commonly utilized as a medicinal herb with its rhizomes, mainly used to regulate the immune function of the human body. However, relatively few studies have investigated its active components and potential mechanisms of action in vivo.Methods: First, the chemical composition in vitro was identified and analyzed using the UPLC-Q-TOF MS/MS technique. Cyclophosphamide (CTX) was then administered intraperitoneally to rats to establish an immunosuppression model. Physiological and biochemical parameters, organ indices, and histopathological findings were evaluated for efficacy. Subsequently, potential biomarkers in rat serum were identified using multivariate statistical analysis and enriched and topologized using online platforms such as MetaboAnalyst and KEGG to reveal the critical metabolic pathways and their roles in the immunomodulatory network. Finally, the integrated analysis of components in vivo and in vitro, along with metabolic pathways, was performed using network pharmacology and molecular docking technology to elucidate the mechanisms of their roles in organismal immunity.Results: A total of 28 chemical components in vitro were identified, while pharmacodynamic experiments confirmed the immunomodulatory effects of Yantuo, especially in the high-dose administration group. Metabolomics analysis showed that 37 potential immune-related biomarkers were identified in positive and negative ion modes, involving 16 metabolic pathways such as arginine biosynthesis, pyrimidine metabolism, and riboflavin metabolism. The results of network pharmacology and molecular docking indicated that Yantuo may affect 7-O-galloyl-catechin, Cynaroside, Quercetin-7-O-beta-D-glucopyranoside, and 1.6-bis-O-galloyl-beta-D-glucose through interactions with the immune system, with significant pathways of action including galactose metabolism, glycolysis/gluconeogenesis, pyrimidine metabolism, and riboflavin metabolism.Conclusion: In our experiments, we confirmed the organismal modulatory effect of Yantuo on immunocompromised rats, clarified the key components, target proteins, and pathways of its possible action, and provided possibilities for follow-up studies. Keywords: immunosuppression, Yantuo, metabolomics, network pharmacology, molecular docking